THE IMPORTANCE OF LISTENING SKILLS: A FOUNDATION FOR EFFECTIVE COMMUNICATION AND LEARNING (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
Listening is one of the most essential yet often underestimated skills in human communication. As an active process of receiving, constructing meaning, and responding to spoken messages, listening plays a critical role in both academic achievement and interpersonal interaction. It enables learners to acquire knowledge, develop critical thinking, and engage meaningfully in social and professional environments.Despite its importance, listening is frequently undervalued in comparison with speaking or writing skills. However, research emphasizes that effective listening fosters empathy, enhances mutual understanding, and promotes successful collaboration. In today’s increasingly interconnected and multicultural world, the ability to listen attentively and analytically is essential for fostering global communication and lifelong learning.